The effects of sorghum dried distillers grains with solubles on finishing pig growth performance, carcass characteristics, and fat quality - K M Sotak; Terry A Houser; Michael D Tokach; Steven S Dritz; B Goehring; G R Skaar; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 288 finishing pigs (PIC TR4 × 1050, initially 129.6 lb) were used in a 73-d study to determine the effects of increasing sorghum dried distillers grains with solubles (DDGS) in sorghum- or corn-based diets on finishing pig growth performance, carcass characteristics, and fat quality. Pigs were allotted to 1 of 6 dietary treatments in a completely randomized design based on initial pen weight. The dietary treatments included sorghum-based diets with sorghum DDGS included at 0, 15, 30, or 45%; a sorghum-based diet with 30% corn DDGS; and a corn-based diet with 30% corn DDGS. Overall (d 0 to 73), increasing sorghum DDGS from 0 to 45% reduced (linear, P<0.04) ADG and ADFI. Increasing sorghum DDGS increased (linear, P<0.01) backfat iodine value (IV), and fat color became less red (a*; linear, P<0.01) and tended to be less yellow (b*; linear, P<0.06). No differences were observed in growth performance among pigs fed corn- or sorghum-based diets with 30% corn DDGS along with similar carcass characteristics, backfat, loin depth, fat-free lean index (FFLI), HCW, carcass yield, and backfat IV. Pigs fed sorghum-based diets with either 30% sorghum or corn DDGS had similar ADG, ADFI, and F/G, as well as similar carcass characteristics; however, pigs fed 30% sorghum DDGS had decreased (P<0.01) backfat IV and fat color that was more white (L*) and less yellow (b*) in color than pigs fed 30% corn DDGS. We observed similar ADG, ADFI, and F/G, as well as carcass characteristics, for pigs fed corn- or sorghum-based diets with 30% DDGS. Backfat IV was greater in pigs fed increasing DDGS, with a notable increase in pigs fed corn DDGS compared with those fed sorghum DDGS. Feeding sorghum DDGS produces pork fat that is lighter in color and less yellow than those fed corn DDGS, which may have an important role in pork export markets.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Corn; DDGS; Finishing pig; Sorghum